Catches of Fishes by Variocoloured Trammel net Upon the Influences of Lunar Rhythm - Chaichan Mahasawasde; Likhit Chuchit (Agriculture and Natural Resources, 1990)
An experiment of the catches of fish by white, green and violet trammel nets at the depth of 3 meters, was conducted at night around Sriracha Bay at Sriracha Fisheries Research Station during 2-3 days before and after full moon and new moon in June to September, 1987. Factorial experiment in randomized block design was engaged. The results revealed that the catch efficiencies of white, green and violet trammel nets show no significant differences upon the lunar periodicity. In the full moon night, a large number of silver biddy ( Gerres filamentosus ) was caught with highly significant against pony fish ( Leiognathus brevirostris ) and swimming crab ( Portunus pelagicus ) . In the new moon night, a lot of silver biddy and swimming crab were caught with highly significant against pony fish. The efficiency of white trammel net was the best in full moon operation for shrimps and cephalopod and the efficiency of green trammel net operation was the best for aquatic animals even though they showed no significant differences among the three colour of them.